Heat-induced changes in milk fat and milk fat globules and its derived effects on acid dairy gelation – A review. (April 2022) - Wiking, L.; Gregersen, S.B.; Hansen, S.F.; Hammershøj, M.
Abstract: Heating of milk induces several molecular changes around the milk fat globule and its membrane. This review focuses on whey protein association to the milk fat globule membrane during heating and describes the molecular mechanisms. The knowledge gaps about the exact binding types between MFGM proteins, membrane lipids and the plasma proteins in milk is also pointed out. Further, the interactions between heating and other processing steps such as membrane filtration and homogenisation is reviewed. In full fat yoghurt products, the heat treatment is important to optimise the firmness of the products as the covering of proteins around the milk fat globules is critical for the binding into the protein-gel. The review also deals with the heat deactivation of enzymes related to the milk fat such as lipoprotein lipase and proteases; and its impact on of immunoglobulins derived agglutinations of milk fat globules.